Forecasting international tourism demand: The evidence of Macedonia - Biljana Petrevska (UTMS Journal of Economics, 2012)
The paper makes an attempt to provide estimation of foreign tourism demand by 2014, by investigating the case of Macedonia. The author applies the Box-Jenkins methodology and tests several alternative specifications in the modeling of original time series. Upon the outcomes of standard indicators for accuracy testing, the research identifies the model of ARIMA(1.1.1) with a dummy, as the most appropriate. According to the four-year-forecasts, it is expected a 25% increase of the international tourist arrivals. Although the suggested model cannot explain the driving factors behind the results, the projected values can assist in mitigating the potential negative impacts as well as in the preparation of tourism development plan in Macedonia.
Keywords: C53; L83; 330; forecasting; Box-Jenkins methodology; international tourism demand; Macedonia